Pemetaan Kajian Sumber Daya Manusia dan Produktivitas Pendidikan: Analisis Bibliometrik - Paulinus Kanisius Ndoa; Djam’an Satori; Endang Herawan; Cepi Triatna (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: This study presents a comprehensive bibliometric analysis of global research trends concerning human resources and productivity in education. Drawing upon 660 Scopus-indexed documents published between 2000 and 2025, the analysis employs quantitative mapping techniques using VOSviewer to uncover patterns in publication growth, influential authors and institutions, dominant research themes, and keyword co-occurrence networks. The findings reveal a consistent and significant rise in scholarly output, especially in areas such as teacher performance, educational leadership, and digital transformation. The co-occurrence analysis highlights strong linkages between human capital development strategies and institutional productivity, suggesting a convergence of educational management, organizational psychology, and public policy perspectives. Additionally, emerging themes emphasize the increasing importance of digital competencies, professional well-being, and workforce agility, particularly in the context of educational reform and post-pandemic challenges. Despite growing interest, the analysis also reveals fragmented research collaboration across countries and limited integration between developed and developing contexts. This study contributes theoretically by reinforcing the relevance of human capital theory in modern educational discourse and offers practical implications for policymakers and educational leaders. It recommends incorporating bibliometric insights into strategic planning, capacity-building initiatives, and inclusive policy frameworks aimed at optimizing human resources in education. By providing a data-informed foundation, the study enhances the understanding of productivity drivers in the education sector and supports evidence-based decision-making for sustainable development.. Keywords: Human Resources; Educational Productivity; Teacher Performance; Digital Transformation; Bibliometric Analysis; VOSViewer. Abstrak: Penelitian ini menyajikan analisis bibliometrik komprehensif terhadap tren global dalam riset sumber daya manusia (SDM) dan produktivitas di bidang pendidikan. Berdasarkan 660 dokumen yang terindeks Scopus antara tahun 2000 hingga 2025, penelitian ini menggunakan teknik pemetaan kuantitatif dengan perangkat lunak VOSviewer untuk mengidentifikasi pola pertumbuhan publikasi, penulis dan institusi yang berpengaruh, tema-tema utama, serta jaringan keterkaitan kata kunci. Hasil analisis menunjukkan peningkatan signifikan dalam jumlah dan keragaman publikasi, terutama pada topik kinerja guru, kepemimpinan pendidikan, dan transformasi digital. Temuan ini mengindikasikan keterkaitan erat antara strategi pengembangan modal manusia dan produktivitas kelembagaan, serta mencerminkan sinergi antara manajemen pendidikan, psikologi organisasi, dan kebijakan publik. Tema-tema baru yang muncul menekankan pentingnya penguasaan kompetensi digital, kesejahteraan profesional, dan ketahanan tenaga kerja, terutama dalam menghadapi tantangan pasca-pandemi dan reformasi pendidikan. Namun, kolaborasi riset antarnegara masih menunjukkan fragmentasi, dengan keterlibatan yang belum merata antara negara maju dan berkembang. Secara teoritis, studi ini memperkuat relevansi teori modal manusia dalam konteks pendidikan kontemporer. Secara praktis, studi ini merekomendasikan pemanfaatan hasil analisis bibliometrik untuk mendukung perencanaan strategis, penguatan kapasitas SDM, dan perumusan kebijakan yang inklusif dan berbasis data. Dengan demikian, penelitian ini memberikan landasan informasi yang kuat untuk pengambilan keputusan yang berkelanjutan di sektor pendidikan. Kata kunci: Sumber Daya Manusia; Produktivitas Pendidikan; Kinerja Guru; Transformasi Digital; Analisis Bibliometrik; VOSViewe